Physostigmine in Anticholinergic Poisoning: An Old Antidote With Resurgence - Blackstone, Nicholas G (Cureus, 2020)
Physostigmine is a cholinesterase inhibitor used therapeutically in patients with anticholinergic delirium that is so severe that intubation may be required for airway protection. Given that a wide variety of medications have anticholinergic properties, and the current standard of care is typically a central nervous system depressant, hospitalizations are often lengthy and normally require a critical-care level of attention. Despite this, physostigmine is often underutilized and poorly understood in the clinical setting. We report a case of a 43-year-old female who presented to the emergency department one hour after ingesting approximately 150 tablets of diphenhydramine in a suicide attempt. She was treated with benzodiazepines with minimal success, and airway protection became imminent as her mentation continued to decline. Through the use of physostigmine, we were able to save this patient from endotracheal intubation and the potential complications of mechanical ventilation.